Peran Bank Syariah dalam Keuangan Sosial Islam: The Role of Islamic Banks in Islamic Social Finance - Bayu Sudrajat; Firman Dermawan; Hasilan; Meli Tri Nur Azkia (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2026)
This study explores in depth the role of Islamic banks in advancing Islamic Social Finance (ISF), which includes zakat, waqf, ṣadaqah, qardhul ḥasan, and other social-based Islamic financial instruments. The objective of this research is to analyze the strategic functions of Islamic banks in supporting social welfare, reducing socio-economic disparities, and fostering sustainable community empowerment through Sharia-compliant mechanisms. The study employs a qualitative descriptive method by analyzing relevant scholarly works, economic literature, financial regulations, and institutional practices. The findings reveal that Islamic banks serve as key institutions in mobilizing social funds, managing zakat and waqf schemes, initiating benevolent financing, and promoting the professionalization and digitalization of social finance management. Islamic banks are also found to play important roles in enhancing transparency, increasing financial inclusion, improving governance, and ensuring Sharia supervisory compliance. The study concludes that Islamic banks should not be perceived merely as commercial intermediaries, but rather as socio-economic development agents that significantly contribute to social justice and welfare within the Islamic economic system.